2018
DOI: 10.1088/1741-2552/aace8c
|View full text |Cite
|
Sign up to set email alerts
|

EEGNet: a compact convolutional neural network for EEG-based brain–computer interfaces

Abstract: Our results suggest that EEGNet is robust enough to learn a wide variety of interpretable features over a range of BCI tasks. Our models can be found at: https://github.com/vlawhern/arl-eegmodels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
1,940
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 2,295 publications
(2,238 citation statements)
references
References 109 publications
16
1,940
1
3
Order By: Relevance
“…To understand class-specific spectral characteristics in the EEG recordings, we analyzed band powers in five frequency ranges: delta (0-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13)(14), low beta (14)(15)(16)(17)(18)(19)(20), high beta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and low gamma .…”
Section: Visualizations Of the Spectral Differences Between Normalmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand class-specific spectral characteristics in the EEG recordings, we analyzed band powers in five frequency ranges: delta (0-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13)(14), low beta (14)(15)(16)(17)(18)(19)(20), high beta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and low gamma .…”
Section: Visualizations Of the Spectral Differences Between Normalmentioning
confidence: 99%
“…These ConvNets exploit the hierarchical structure present in many natural signals. Recently, deep ConvNets trained end-to-end were, for example, able to more accurately diagnose skin cancer types from images than human dermatologists [9] and could segment retinal vessels better than human annotators [10].Deep ConvNets are nowadays also being applied to EEG analyses, such as decoding task-related information from EEG [11][12][13][14][15][16]. We have recently developed and validated the Braindecode toolbox1 for this purpose, and showed that the performance of deep ConvNets trained end-to-end is comparable to that of algorithms using hand-engineered features to decode task-related information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As found out by Lawhern,7,8 with extremely less number of parameters, training is faster and overfitting is very less. As found out by Lawhern,7,8 with extremely less number of parameters, training is faster and overfitting is very less.…”
Section: Using Deep Learning Structurementioning
confidence: 95%
“…3 Few researchers also suggested some frameworks in analyzing the various methods in the prediction of epileptic seizures. 7,8 Weighted frequencies were calculated and used to make comparisons between normal and seizure signals using statistical methods like t-test. 5 Analysis of the IMF helped researchers in discriminating against the normal EEG and seizure EEG very efficiently, but the possibility of prediction some minutes or hour before the onset of seizure was not discussed.…”
Section: Related Workmentioning
confidence: 99%